PERAN GURU DALAM MENGATASI KENAKALAN SISWA KELAS IV DI SD NEGERI 02 NAMROLE - Wailusu, Rahmawati; Ritiauw, Samuel Patra; Mahananingtyas, Elsinora (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
This research aims to find out "The Role of Teachers in Overcoming Class IV Student Delinquency at SD Negeri 02 Namrole". The research method used is qualitative. The sample used in this research was class IV teachers with a sample size of 4 teachers. Data collection methods are carried out by interviews, documentation, observation methods. Based on the results of interviews conducted by researchers with resource persons, researchers found data that class teachers and subject teachers in class IV had sufficient understanding of the situation and circumstances of class IV students.